Aqueous angiography in pre‐glaucomatous and glaucomatous ADAMTS10‐mutant canine eyes: A pilot study. (1st November 2021) - Burn, Jessica B.; Huang, Alex S.; Weber, Arthur; Komáromy, András M.; Pirie, Christopher G.
Abstract: Objective: To evaluate intravenous scleral and intracameral aqueous angiography in normotensive ( n  = 4) and hypertensive glaucomatous ( n  = 6) ADAMTS10 ‐mutant canine eyes. Animals studied: Ten ADAMTS10 ‐mutant dogs were used in this study. Procedures: Dogs were sedated and one eye from each dog underwent scleral angiography following intravenous injection of 0.25% indocyanine green (ICG). After a 24‐h recovery period, the same eye underwent aqueous angiography via intracameral administration of ICG. Imaging of identical scleral sectors from the same eye was performed using a Heidelberg Spectralis ® Confocal Scanning Laser Ophthalmoscope. Intrascleral vessel depth and lumen diameters were measured using Heidelberg Spectralis ® optical coherence tomography and computer software. Results: Scleral angiography permitted visualization of vascular components associated with conventional aqueous humor outflow pathways with an average time from injection to fluorescence of 35.8 ± 10.6 s (mean ± SD). Two normotensive eyes (2/10;20%) demonstrated turbulent dye movement, while 4 hypertensive eyes (4/10;40%) exhibited laminar flow. Aqueous angiography demonstrated dye fluorescence within the post‐trabecular conventional aqueous humor outflow pathways in all 10 eyes at 34.3 ± 11.0 s post‐injection. Sectoral and dynamic outflow patterns were observed primarily within the superotemporal sector in nine eyes (9/10; 90%). Seven eyes (7/10; 70%) demonstrated pulsatile dye movement and five eyes (5/10; 50%) exhibited laminar flow. The degree of laminar movement of dye was greatest in hypertensive eyes. Vessel lumen diameters measured 133.85 ± 28.36 µm and 161.18 ± 6.02 µm in hypertensive and normotensive eyes, respectively. Conclusions: Aqueous angiography allowed for visualization of fluorescent dye in the superotemporal sclera. Laminar flow and smaller lumen vessels were observed mainly in hypertensive eyes.